2017
DOI: 10.1007/s10142-017-0546-z
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid, sucrose, and auxin coordinately regulate berry ripening process of the Fujiminori grape

Abstract: The aim of this study was to examine the effect of abscisic acid (ABA), sucrose, and auxin on grape fruit development and to assess the mechanism of these three factors on the grape fruit ripening process. Different concentrations of ABA, sucrose, and auxin were used to treat the grape fruit, and the ripening-related indices, such as physiological and molecular level parameters, were analyzed. The activity of BG protein activity was analyzed during the fruit development. Sucrose, ABA, and auxin influenced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 46 publications
3
63
1
1
Order By: Relevance
“…Similar results have been reported for some grape varieties (Lecourieux et al, 2014). Recently, Jia et al (2017) showed that treatments with sugars, especially sucrose, induced anthocyanin biosynthesis and fruit softening in detached Fujiminori grapes. Also, Zheng et al (2009) demonstrated elevated anthocyanin biosynthesis and accumulation in Cabernet Sauvignon grape berry disks after immersion in solutions containing 50–200 mM glucose, sucrose, or fructose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results have been reported for some grape varieties (Lecourieux et al, 2014). Recently, Jia et al (2017) showed that treatments with sugars, especially sucrose, induced anthocyanin biosynthesis and fruit softening in detached Fujiminori grapes. Also, Zheng et al (2009) demonstrated elevated anthocyanin biosynthesis and accumulation in Cabernet Sauvignon grape berry disks after immersion in solutions containing 50–200 mM glucose, sucrose, or fructose.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, sucrose in co-operation with ABA are indicated as the core signaling molecules regulating strawberry fruit ripening (Jia et al, 2011, 2013b). The coordinated regulation of fruit ripening by ABA and sucrose has recently been suggested also for grapes (Jia et al, 2017). …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…5). In that respect, previous studies reported that auxin reduces the sugar content in fruits [48]. However, the precise association of the genes CmAUXRF1, CmAUXRF2 and CmAUXRS with the sugar pathway requires further studies.…”
Section: Global Characteristics Of the 'Yellow' Non-climacteric Melonmentioning
confidence: 94%
“…In citrus, 1-MCP repressed genes involved in starch synthesis and degradation and increased the expression levels of SuSy genes (Estables-Ortiz et al, 2016). In grapes, and another non-climacteric fruit, strawberry, it has been proposed that sucrose functions as a signal that acts upstream of the ABA signaling pathway, thus playing an important role in the regulation of fruit ripening (Jia et al, 2013;Jia et al, 2017).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%